Work for Social Justice from Education - F. Javier Murillo; Reyes Hernandez-Castilla (Universidad Autónoma de Madrid, 2016)
Since Plato in his Republic raised Justice as one of the fundamental virtues, the basis of others, has been considered as one of the goals to be achieved by society. However, it was in the first industrial revolution when this concept, already with its adjective Social, takes on all its strength and meaning. In these last decades, the concern increases, in such a way that Julián Marías went on to say that "the 20th century would not be understandable without that term" (Marías, 1974: 7). With globalization, migratory movements and the crisis, inequalities become more complex: gender, social class, culture, mother tongue, ability, sexual orientation ... they become causes of exclusion. The gap between North and South, rich and poor, native-immigrants, more able-less capable ... is growing, but also the sensitivity to build a more just society. With this background, the citizen movement, already international, of the Indignados is more than justified. However, in addition to being outraged, we must act. And in that context, education plays a fundamental role. Far are the pessimistic views that the school is a mere instrument of social reproduction, as defended both the Coleman (1966) and Plowden (1969) and the French sociologists (Bourdieu and Paseron, 1972). The school, on the one hand, is the instrument that society uses to legitimize injustices through its competence to grant and deny degrees (Connell, 1997) and, on the other hand, its ability to compensate for the differences of departure has been demonstrated. and contribute to social mobility.